Prehospital treatment of severely burned patients: a retrospective analysis of patients admitted to the Berlin burn centre - Josuttis, David; Kruse, Marianne; Plettig, Philip; Lenz, Ida Katinka; Gümbel, Denis Dominic; Hartmann, Bernd; Kuepper, Simon Steffan; Gebhardt, Volker; Schmittner, Marc (Scandinavian journal of trauma, resuscitation and emergency medicine, 2024)
Prehospital management of severely burned patients is extremely challenging. It should include adequate analgesia, decision-making on the necessity of prehospital endotracheal intubation and the administration of crystalloid fluids. Guidelines recommend immediate transport to specialised burn centres when certain criteria are met. To date, there is still insufficient knowledge on the characteristics of prehospital emergency treatment. We sought to investigate the current practice and its potential effects on patient outcome.